2017
DOI: 10.1111/bcpt.12751
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometry‐Based Tools to Characterize DNA–Protein Cross‐Linking by Bis‐Electrophiles

Abstract: DNA-protein cross-links (DPCs) are unusually bulky DNA adducts that form in cells as a result of exposure to endogenous and exogenous agents including reactive oxygen species, ultraviolet light, ionizing radiation, environmental agents (e.g. transition metals, formaldehyde, 1,2-dibromoethane, 1,3-butadiene), and common chemotherapeutic agents. Covalent DPCs are cytotoxic and mutagenic due to their ability to interfere with faithful DNA replication and prevent accurate gene expression. Key to our understanding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 112 publications
(156 reference statements)
1
19
0
Order By: Relevance
“…Although chemotherapeutics, such as cisplatin derivatives and nitrogen mustards, are mainly known to form DNA adducts and DNA ICLs, they can also form DPCs [ 16 ]. Cisplatin can induce DPCs by attacking the N7 atom of purine bases, which can then be connected to cysteine, arginine, and lysine side chains by a subsequent nucleophilic attack on the platinum center ( Fig.…”
Section: Dna-protein Crosslinks: a Diverse Class Of Lesionsmentioning
confidence: 99%
“…Although chemotherapeutics, such as cisplatin derivatives and nitrogen mustards, are mainly known to form DNA adducts and DNA ICLs, they can also form DPCs [ 16 ]. Cisplatin can induce DPCs by attacking the N7 atom of purine bases, which can then be connected to cysteine, arginine, and lysine side chains by a subsequent nucleophilic attack on the platinum center ( Fig.…”
Section: Dna-protein Crosslinks: a Diverse Class Of Lesionsmentioning
confidence: 99%
“…Because of the presence of two epoxy moieties in the molecule, DEB not only has stronger reactivity in comparison with EB and EBD [ 89 91 ], but also can form DNA cross-links [ 7 , 83 , 92 96 ] and DNA-protein cross-links [ 97 ]. As a result, clastogenicity of DEB is very high; among ~100 IARC carcinogens (Group 1, 2A, and 2B), DEB shows highest level of micronucleus (MN) induction in mice [ 98 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike other types of DNA damage, DPCs are massively diverse 1 2 . Studies have demonstrated that hundreds of cellular proteins can become crosslinked to DNA and that for each protein there are, in principle, numerous amino acid side chains that could become covalently attached to cellular DNA 3 . In addition, there are numerous chemical attachment points for proteins onto the DNA backbone, including several positions on the nucleotide bases as well as on the ribose sugar 4 5 .…”
Section: Introductionmentioning
confidence: 99%